The influence of spousal interaction and husbands' communication styles on their perception of their participation in family planning in Indonesia Sheilia Novitriani ; Fernando dlC. Paragas, adviser. - Novitriani, Sheilia. 1981- (2018)
"This thesis explores the role of interaction and communication in how married men perceive their participation in Indonesia's family planning program (FPP). In a patriarchic society sich as South Kalimantan, where this study was conducted, husbands are afforded a primary position as the family's key decision maker. Since men perceive family planning as the domain of women, their stance towards and subscription to it remains unclear. Moreover, husbands and wives have distinct interactional and communication styles, which can then preclude a clear discussion of family planning. This survey of 400 husbands finds empathetic interaction and communication between the husbands and wives simultaneously influence the husband's perception of their participation in the FPP. Moreover, the husbands' knowledge of family planning significantly contributes to the shaping of their perception of their participation in the FPP. Intimate conversation also has a significant contribution to the husbands and wives' interaction and communication which eventually affect the way husbands perceive their participation in the FPP. The study concludes that open interaction and emphatic communication are a prerequisite in shaping the positive perception of men's participation in the program. It offers theoretical, methodological and practical recommendations for the FPP in Indonesia."